Linear IgA dermatosis associated with ulcerative colitis: complete and sustained remission after total colectomy - Thiago Jeunon de Sousa Vargas; Mônica Fialho; Luiza Tavares dos Santos; Palmira Assis de Jesus Barreto Rodrigues; Ana Luisa Bittencourt Sampaio Jeunon Vargas; Maria Auxiliadora Jeunon Sousa (Sociedade Brasileira de Dermatologia, 2013)
Linear IgA dermatosis has been increasingly associated with inflammatory bowel diseases, particularly ulcerative colitis. A 13-year-old male patient with an 11-month history of ulcerative colitis developed vesicles, pustules and erosions on the skin of the face, trunk and buttocks and in the oral mucosa. The work-up revealed a neutrophil-rich sub-epidermal bullous disease and linear deposition of IgA along the dermoepidermal junction, establishing the diagnosis of linear IgA dermatosis. The patient experienced unsatisfactory partial control of skin and intestinal symptoms despite the use of adalimumab, mesalazine, prednisone and dapsone for some months. After total colectomy, he presented complete remission of skin lesions, with no need of medications during two years of follow-up. A review of previously reported cases of the association is provided here and the role of ulcerative colitis in triggering linear IgA dermatosis is discussed.